Durability prediction analysis on mechanical properties of GFRP upon immersion in water at ambient temperature. Issue 1 (1st January 2021) - Kowshik, Suhas; M C, Gowrishankar; Shettar, Manjunath; Bhat, Ritesh; B M, Gurumurthy
Abstract: In this article, the influence of varying the weight percentage of glass fiber on the water uptake, tensile and flexural strengths of glass fiber-polyester composites are evaluated. The composites are fabricated by hand lay-up process and further subjected to water immersion for a varied time period (between 0 and 180 days) at ambient temperature. Tests for Tensile and flexural strengths are conducted according to the specifications of ASTM. The test results indicate that the increase in the weight percentage of glass fiber enhanced the tensile strength (by 9–17%) and flexural strength (by 10–17%). Higher retention rates of tensile and flexural strengths are detected at higher weight percentages of glass fiber. An 86% retention rate of tensile strength and a 92% retention rate of flexural strength is detected with 50 wt.% glass fiber reinforced, water immersed specimen. The causes for the failure of specimens under tensile load are discovered with the help of SEM images. The experimental data and the data generated by the ExpDec1 model are significantly closer to each other, which indicates that the ExpDec1 model can be used for predicting the values based on the days of immersion.